Detection of cyprinid herpesvirus 2 by loop-mediated isothermal amplification in combination with a lateral flow dipstick. (April 2020) - Li, Yanli; Lin, Feng; Sun, Lihui; Huang, Aixia; Chen, Jianming; Hao, Guijie; Yuan, Xuemei; Zhang, Haiqi; Su, Shengqi
Abstract: We developed a convenient technique to detect Herpesviral haematopoietic necrosis attributed to cyprinid herpes virus 2 (CyHV-2), a serious disease of Crucian carp and goldfish related to high mortality. In the present study, we employed a lateral flow dipstick (LAMP-LFD) to present a loop-mediated isothermal amplification assay. The specificity was ascertained via other six viruses, and the sensitivity was compared using PCR method, which are the reaction conditions changes for the method improved. The results revealed that CyHV-2 performance was observable at 64 °C in a separated tube within 60 min, when the samples hybridized using an FITC-labeled probe. As the LAMP-LFD method's specificity was high, with its sensitivity identical to that of traditional PCR, the overall DNA collected revealed the lowest detection limit of 0.18 pg/μl from goldfish diseased by CyHV-2. In summary, the development of LAMP-LFD's method does not require expensive instruments, and it can be regarded as a fast, simple, and reliable method for CyHV-2 detection. Highlights: The LAMP-LFD for detecting CyHV-2 was developed by amplification at 64 °C for 60 min. The LAMP-LFD was specific for CyHV-2. Sensitivity of LAMP-LFD was not low in comparison to PCR. The LAMP-LFD would be a simple, rapid and reliable method for detection of CyHV-2.